Prevalence and predictors of self-medication practices among adult household members in Hosanna town, Hadiya zone, central Ethiopia - Sentayehu Admasu Saliya; Awoke Girma Hailu; Sisay Foga Sebro; Misgana Desalegn Menesho (BMC Public Health)
Abstract Background Self-medication is a global health concern with serious public health implications. Excessive and inappropriate self-medication practice can lead to recurrent infections and increased antibiotic resistance, which is a major problem impacting morbidity and mortality worldwide. Despite the significance of this issue, no single study has been conducted on self-medication practices in the study area, to the best of the researchers’ knowledge. Objective To assess prevalence and predictors of self-medication practices among adult household members in hosanna town hadiya zone, central Ethiopia 2024. Methods A community-based cross-sectional study was conducted from March 1–30, 2024, among 566 randomly selected households in Central Ethiopia. Households were chosen using a simple random sampling technique. Both bivariable and multivariable binary logistic regressions were used to assess the explanatory variables associated with self-medication practices. Adjusted odds ratios (AOR) with a p-value < 0.05 at a 95% confidence interval were considered statistically significant. Results Out of the 566 study participants, 546 respondents were interviewed, yielding a response rate of 96.46%. Among the study participants, 338 (61.9%) with a 95% CI of (57.8–65.9) practiced self-medication in the past two months. Age of respondents ≥ 48 years (AOR = 2.76, 95% CI: (1.27, 5.99)), being married (AOR = 3.24, 95% CI: (2.0-5.26)), having a family size ≥ four members (AOR = 1.69, 95% CI: (1.00-2.87)), and not being a member of a health insurance scheme (AOR = 3.13, 95% CI: (1.95–5.04)) were significantly associated with self-medication practices. Conclusion and recommendations The prevalence of self-medication practice in the study area was relatively high. Self-medication practices were associated with the age of respondents, marital status, family size, and health insurance membership. Public health education and awareness campaigns should be strengthened to emphasize safe and responsible self-medication practices, particularly among older adults and those living in larger families.